A series of MOUs signed between CIAT with academic, management and development partners to adopt and boost CCAFS outcomes - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The project work greatly contributed to preparing pathways to boost CCAFS outcomes by signing MOUs with Yen Bai Department of Agriculture and Rural Development (DARD), Vietnam National University of Agriculture (VNUA), FAO, National Target Program on New Rural Development (NTM), and renewing the MOU with Ministry of Agriculture and Rural Development (MARD). This is to enable a common framework to scale out the CCAFS work to all 63 provinces in Vietnam within NTM during 2021-2025